Wound Patterns in Victims of Physical Abuse: A Retrospective Descriptive Analysis at Bhayangkara Sartika Asih Hospital, Indonesia - Andri Andrian Rusman; Teja Koswara; Jabal Cahyo Wibowo (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Physical violence remains a global public health concern, with limited Indonesia-specific data on non-fatal injuries. This study aims to describe the characteristics of victims of physical abuse based on age, sex, and wound patterns using forensic medical reports to support public health strategies and forensic practices. A retrospective descriptive study was conducted using 150 Visum et Repertum (VeR) reports from living victims of physical violence treated at Bhayangkara Sartika Asih Hospital, Bandung, in 2022. Reports were selected through purposive sampling, including only those with complete documentation; cases involving deceased victims or unrelated to physical violence were excluded. Results showed that the most affected age group was 17-25 years (36.67%). Males represented the majority of victims (95.3%). The most common type of injury was bruises (34.52%), followed by abrasions (33.33%) and lacerations (21.03%). Among males, 83 (58%) sustained bruises, while among females, 5 (71%) had abrasions. Head injuries were predominant, with 30 cases (20%) having single wounds and 89 cases (59.3%) multiple wounds. These findings highlight the importance of targeted interventions for young males and suggest that injury surveillance systems should better capture non-fatal violence trends. The observed patterns may reflect social dynamics and risk behaviors prevalent in this demographic group, warranting further investigation Keyword: Physical Violence, Trauma, Wound Pattern, Forensic Medicine